Understanding the large deformation response of paste-like 3D food printing inks - Bugday Yagmur; Alicke Alexandra; Anderson Patrick; van der Sman Ruud (Applied Rheology)
Extrusion-based three-dimensional (3D) food printing is an emerging technique, relying crucially on the rheological behavior of the ink for success. This study aims to understand the rheological properties of the paste-like 3D food printing inks near the processing conditions. Experimental artifacts, particularly the edge fracture at high deformations, are a common challenge when working with pastes. While steady shearing is the most informative measurement, it is not practical due to experiential artifacts. We characterized the rheology of these inks with oscillatory measurements, described the deformation response with a constitutive model, and translated the information from oscillatory testing to steady shearing. The novel constitutive model is a generalization of the Oldroyd-B model using a shear-rate-dependent viscosity following Herschel Bulkley. The model parameters were estimated by non-linear least-squares fitting. The constitutive model successfully predicted the sample response at large deformations and the steady-shear flow response, such as those encountered in 3D food printing. The applicability of the methodology can be extended for different materials that are challenging to characterize. We explored methods to measure the rheological properties of paste-like materials prone to edge fracture, aiming for an accurate description of their response under processing.